2011
DOI: 10.1097/icb.0b013e3181c59973
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Rapid Resolution of Posttrabeculectomy Exudative Retinal Detachment With Only Topical Corticosteroid Therapy in a Case of Nanopthalmos

Abstract: Topical corticoid therapy alone may be sufficient to achieve quick resolution of exudative retinal detachment secondary to glaucoma surgery in nanophthalmic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
“…31 Medical therapy with oral corticosteroids in uveal effusion syndrome is well established but was deemed ineffective in nanophthalmos. 10,11 Elgin et al 9 described a patient with nanophthalmos and mild exudative RD that resolved rapidly after administration of the topical corticosteroid alone. The authors suggested that the corticosteroid reduced inflammation and stabilized the blood-ocular barrier, thereby improving regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that some treatments can effectively treat ERD in patients with nanophthalmos; these treatments include corticosteroid therapy, NSAID therapy, and surgical procedures. 6 , 7 , 10 , 11 The mechanism by which ERD is resolved by corticosteroids is a matter of speculation. Ufuk et al.…”
Section: Discussionmentioning
confidence: 99%
“… 10 suggested that treatment with high doses of corticosteroid reduces inflammation, and that this may be related to the ability of corticosteroids to stabilize the blood–ocular barrier, thereby improving regression. Those authors described a patient with nanophthalmos 10 in whom ERD was unusually rapidly resolved by treatment with topical corticosteroid alone. However, in our patient, during the initial instance of ERD, the patient did not respond to steroids, and we therefore employed a surgical approach.…”
Section: Discussionmentioning
confidence: 99%